The stormchasers : a novel - Blum, Jenna (Dutton, 2010)
Twenty years after her bipolar brother's penchant for chasing tornadoes leads to deadly consequences, Karena Jorge finds out that he has escaped from a psychiatric ward, prompting her to join a band of professional stormchasers in hope of finding her disturbed brother.